The Relationship Between Public Service Motivation and Affective Commitment in the Public Sector Change: A Moderated Mediation Model - Sun, Sirui (Frontiers in Psychology, 2021)
How can public organizations promote change recipients’ affective commitment to public sector change? Based on socially desirable responding theory, this study explores the theoretical mechanism and boundary effect of the relationship between public service motivation and affective commitment to change. By conducting a survey of 465 front-line public employees in an eastern Chinese city undergoing public sector change, this study found that voice behavior partially mediates the relationship between public service motivation and affective commitment to change. Superficial harmony also negatively moderates the relationship between public service motivation and affective commitment to change through the mediation of voice behavior. This study mainly contributes to our understanding of the theoretical mechanism and the conditional effect of change recipients’ affective commitment during public sector change.